Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T15:13:50+01:00
B=6
c=2*b=2*6=12
a=?

Twierdzenie Pitagorasa:
a<kwadrat> + b<kwadrat> = c<kwadrat>
a<kwadrat>=c<kwadrat> - b<kwadrat>
a<kwadrat> = 12<kwadrat> - 6<kwadrat>
a<kwadrat>=144-36
a<kwadrat>=108
a=6<pierwiastek>z 3


Obw.=a+b+c
Obw.=6<pierwiastek>z 3 + 6 + 12
Obw.= 24<pierwiastek>z 3
1 5 1
2009-12-13T18:08:38+01:00
B=6
c=2*b=2*6=12
a=?

Twierdzenie Pitagorasa:
a<kwadrat> + b<kwadrat> = c<kwadrat>
a<kwadrat>=c<kwadrat> - b<kwadrat>
a<kwadrat> = 12<kwadrat> - 6<kwadrat>
a<kwadrat>=144-36
a<kwadrat>=108
a=6<pierwiastek>z 3


Obw.=a+b+c
Obw.=6<pierwiastek>z 3 + 6 + 12
Obw.= 24<pierwiastek>z
1 5 1